Effect of Ginger and Novafen on menstrual pain: A cross-over trial - Hajar Adib Rad; Zahra Basirat; Fatemeh Bakouei; Ali Akbar Moghadamnia; Soraya Khafri; Zeynab Farhadi Kotenaei; Maryam Nikpour; Somayeh Kazemi (Elsevier, 2018)
Objective: Menstrual pain is a periodic pain which happens during the days of menses. The menstrual disturbances as a health problem among young girls affect not only reproductive, but also psychical health and quality of life. This study was done with the goal of comparing the effect of Ginger and Novafen on the menstrual pain. Materials and methods: This crossover clinical trial study was done in Iran on 168 single girl students 18-26 years old in Babol University of Medical Sciences with primary menstrual pain. The participants were randomly allocated to two groups receiving the drugs Novafen and Ginger. At the beginning of pain, in the two groups 200 mg capsule was given every 6 h for two serial cycles. Pain severity was measured by the visual scale before treatment, 1 h after consuming the drug (for 24 h) and 48 h after the onset of drug. Results: The mean age of participants was 21.83 ± 2.07 years. It has been reported that the intensity of pain from dysmenorrhea decreased in the Novafen and Ginger groups. Before treatment, the average pain intensity in Novafen and Ginger users were 7.12 ± 2.32 and 7.60 ± 1.84, respectively and after treatment pain intensity decreased to 3.10 ± 2.69 and 2.97 ± 2.69, respectively. Differences between two groups each time showed no statistical significance (p > 0.05). Conclusion: Both drugs reduced menstrual pain. Ginger as well as Novafen is effective in relieving pain in girls with primary dysmenorrhea . Therefore, treatment with natural herbal medicine, non-synthetic drug, to reduce primary dysmenorrhea is recommended. Keywords: Novafen, Ginger, Primary dysmenorrhea, Pain relieving